The anatomical hazards of the grip wrist tunnel syndromes - Provyn, S.; van Roy, P.; Clarys, J. P. (Science and Skiing IV, 2008)
OBJECTIVE: Wrist problems, entrapments and paraesthesia in particular, are not uncommon in grip sports, eg: cycling, ski, Pole vaulting etc. to better understand the entrapment symptomatology of the different neurovascular passages at the volar aspect of the wrist, an anatomical revision of its respective tunnel is necessary because confusion and error has increased lately. This study will focus on the ulnar canal. Comparison of the original description of the canal with definitions emanating from scientific papers, anatomical handbooks and internet websites reveal challenging differences, which may create clinical confusion. Cadaver dissections served to document the details of this clinical and functional area.